2009
DOI: 10.1021/ic9001829
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Binding Affinity of Organic Carboxylates to 15-Metallacrown-5 Complexes

Abstract: The reaction of L-phenylalanine hydroxamic acid (H(2)L-pheHA) with copper(II) and lanthanide(III) salts yields 15-Metallacrown-5 structures of the general composition Ln(X)n[Cu(II)(L-pheHA)](5)((3-n)+) where X can represent a wide variety of anions. With five copper ions and one central lanthanide ion, the Ln[15-MC-5] complexes have multiple positions where these anionic guests may bind to the metallacrown host. In addition, these metallacrowns are amphiphilic, containing one face that is primarily hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…[3] A large amount of systematic structural studies of Ln[15MC CuRha -5] complexes derived from α-aminohydroxamic acids with various organic anions have been performed, [4][5][6][7][8][9][10][11][12][13][14] and the affinity of the Ln III ion Scheme 1. It has been demonstrated that the anion affinity for the metallacrown is dependent on the R-substituted hydroximate ligands (Rha).…”
Section: Introductionmentioning
confidence: 99%
“…[3] A large amount of systematic structural studies of Ln[15MC CuRha -5] complexes derived from α-aminohydroxamic acids with various organic anions have been performed, [4][5][6][7][8][9][10][11][12][13][14] and the affinity of the Ln III ion Scheme 1. It has been demonstrated that the anion affinity for the metallacrown is dependent on the R-substituted hydroximate ligands (Rha).…”
Section: Introductionmentioning
confidence: 99%
“…These metals often possess a series of axial coordi-nation sites available for interactions with solvent molecules or co-ligands. [10][11][12] For these reasons MCs have been studied as recognition agents for anions and cations, [13][14][15][16][17][18][19][20] as single molecule magnets, [21][22][23] as building blocks for mesoporous solids, 24 and as luminescent materials for the purpose of in vivo imaging. 25,26 Despite a number of structural and functional studies, numerous aspects which regulate the stability of MCs in solution and the correlation between the species isolated in the solid state and those present in the solution phase are far from being fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 we identified more than 400 articles after searching Web of Science, PubMed, SciDir and OVID databases using ‘isothermal AND titration AND calorimetry’ or ITC or ‘Isothermal Titration Calorimetry’ search terms. These have been classified into the following categories: Pre‐2009 references cited in the text and review articles 1–43 Protein‐protein and protein‐peptide interactions 44–124 Protein/peptide‐small molecule interactions 125–218 Protein/peptide‐metal ion interactions 219–253 Protein/peptide‐nucleic acid interactions 254–273 Protein/peptide‐lipid interactions 274–292 Protein/peptide‐polysaccharide interactions 293–316 Nucleic acid‐small molecule interactions 317–348 Small molecule interactions …”
Section: Introductionmentioning
confidence: 99%